ANALYSIS OF THE BENEFITS AND RISKS OF CANNABIS LEGALIZATION POLICY IN THAILAND AFTER CANNABIS LEGALIZATION IN 2022 – 2024 - Rinda Komala Sari (Jurnal Asia Pacific Studies, 2024)
This study analyzes the benefits and risks of the cannabis legalization policy in Thailand in the period 2022-2024. The main objectives of this study are to evaluate the economic, health, and social impacts of cannabis legalization, and to assess the extent to which this policy supports Thailand's national interests. The research method includes secondary data analysis from government reports and other reliable sources. The results show that cannabis legalization can increase tax revenues, create jobs, and provide health benefits through medical use. However, there are also risks such as potential for increased cannabis use that impact public health, and social changes that must be managed properly. This study provides policy recommendations to maximize benefits and minimize risks, supporting informed and sustainable decision-making. Keywords: Cannabis Legalization, Thailand, Medical Marinjuana